Differences in the oxidative balance of dispersing and non-dispersing individuals: an experimental approach in a passerine bird. Issue 1 (December 2016) - Récapet, Charlotte; Zahariev, Alexandre; Blanc, Stéphane; Arrivé, Mathilde; Criscuolo, François; Bize, Pierre; Doligez, Blandine
Abstract Background Dispersal is often associated with a suite of phenotypic traits that might reduce dispersal costs, but can be energetically costly themselves outside dispersal. Hence, dispersing and philopatric individuals might differ throughout their life cycle in their management of energy production. Because higher energy expenditure can lead to the production of highly reactive oxidative molecules that are deleterious to the organism if left uncontrolled, dispersing and philopatric individuals might differ in their management of oxidative balance. Here, we experimentally increased flight costs during reproduction via a wing load manipulation in female collared flycatchers (Ficedula albicollis ) breeding in a patchy population. We measured the effects of the manipulation on plasmatic markers of oxidative balance and reproductive success in dispersing and philopatric females. Results The impact of the wing load manipulation on the oxidative balance differed according to dispersal status. The concentration of reactive oxygen metabolites (ROMs), a marker of pro-oxidant status, was higher in philopatric than dispersing females in the manipulated group only. Differences between dispersing and philopatric individuals also depended on habitat quality, as measured by local breeding density. In low quality habitats, ROMs as well as nestling body mass were higher in philopatric females compared to dispersing ones. Independently of the manipulation or of habitat quality, plasma antioxidant capacity differed according to dispersal status: philopatric females showed higher antioxidant capacity than dispersing ones. Nestlings raised by philopatric females also had a higher fledging success. Conclusions Our results suggest that dispersing individuals maintain a stable oxidative balance when facing challenging environmental conditions, at the cost of lower reproductive success. Conversely, philopatric individuals increase their effort, and thus oxidative costs, in challenging conditions thereby maintaining their reproductive success. Our study sheds light on energetics and oxidative balance as possible processes underlying phenotypic differences between dispersing and philopatric individuals.